The interconnection of the South African, African and BRICS equities markets - Kabisoso, Muyamba (My University, 2022)
This study aims to find out whether the South African equities market is integrated with the remainder of the BRICS markets and with other selected African markets (Botswana, Nigeria, and Namibia). The sample period used for this study spans from January 2000 – December 2021 for the BRICS markets and February 2004 – December 2021 for the African markets. These periods were chosen to allow for the same number of years before and after the 2008 global financial crisis to be roughly the same without having to separate the two periods. The study makes use of a Vector Autoregression (VAR) model to see whether lagged values of the dependant variable and other variables have some sort of predictive power. The model is used for all the respective market indices as dependent variables. This is then followed by a Granger Causality test, which is used to see in which direction causality flows, or if indeed it flows in both directions (reverse causality). Results point to the existence of interconnection between BRICS markets as there is significant predictive power, with the Russian market appearing to be the most dominant market as it granger causes the majority of markets within the group. Within Africa, interconnection is also present with the Nigerian market showing to be the leader. This all points to the bigger economies leading the groups while the smaller ones follow, with China being an exception within the BRICS group, as it appears to neither significantly affect nor significantly be affected by other markets.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: South African equities market; BRICS markets; African markets